2016
DOI: 10.1016/j.jinf.2016.01.007
|View full text |Cite|
|
Sign up to set email alerts
|

The UK joint specialist societies guideline on the diagnosis and management of acute meningitis and meningococcal sepsis in immunocompetent adults

Abstract: Bacterial meningitis and meningococcal sepsis are rare conditions with high case fatality rates. Early recognition and prompt treatment saves lives. In 1999 the British Infection Society produced a consensus statement for the management of immunocompetent adults with meningitis and meningococcal sepsis. Since 1999 there have been many changes. We therefore set out to produce revised guidelines which provide a standardised evidence-based approach to the management of acute community acquired meningitis and meni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
171
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(180 citation statements)
references
References 261 publications
(221 reference statements)
0
171
0
9
Order By: Relevance
“…Neisseria meningitidis is a leading causative agent of bacterial meningitis and septicemia, particularly in children <5 years old and young adults, 1 and is estimated to cause 500,000 cases and 50,000 deaths globally each year. 2 Of 12 recognized serogroups, six (A, B, C, W, X, and Y) are responsible for nearly all meningococcal disease (MD) globally.…”
Section: Introductionmentioning
confidence: 99%
“…Neisseria meningitidis is a leading causative agent of bacterial meningitis and septicemia, particularly in children <5 years old and young adults, 1 and is estimated to cause 500,000 cases and 50,000 deaths globally each year. 2 Of 12 recognized serogroups, six (A, B, C, W, X, and Y) are responsible for nearly all meningococcal disease (MD) globally.…”
Section: Introductionmentioning
confidence: 99%
“…■ consensus guideline on management of acute meningitis in adults recommends analysis of CSF lactate in these patients. 5 Co-authors of Griffiths' review paper in Clin Med (McGill and Solomon) were also named contributors to this guideline. Measurement of CSF lactate is quick and inexpensive, and can be performed on the same CSF sample taken in the fluoride (grey-top) tube, which is also used to measure CSF glucose concentration.…”
Section: Responsementioning
confidence: 99%
“…Recently, there have been two seminal publications on the diagnosis, treatment, prevention and control of meningococcal disease, namely those prepared by the ‘ Global Meningococcal Initiative ’29 and ‘ The UK Joint Specialist Societies ’ 30. These comprehensive guidelines are excellent reference resources, the key points of which have been summarised in online supplementary Table S4.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…It must be determined that the causative strain is sensitive to the antibiotic of choice, as highlighted by a study on the effect of rifampin on the carriage in military trainees, which reported a reduction in carriage from 65.1% to 10.1% 4 days after treatment, followed by a rapid increase in carriage indicating the emergence of rifampin-resistant strains 40. Ciprofloxacin has also been shown to be effective in eradicating pharyngeal colonisation and is the preferred choice for chemoprophylaxis in the UK Joint Infection guidelines 30 41. It has been reported, however, that a single prophylactic dose of ciprofloxacin, failed to eradicate meningococcal carriage in a small number of military recruits 42…”
Section: Chemoprophylaxismentioning
confidence: 99%